(untitled) (Research, Society and Development, 2022)
The use of urban space, the construction and animation of equipment for physical activities for sport and leisure constitute a fundamental axis of a health and sports leisure policy. Therefore, access to public spaces is extremely important to exercise users’ citizenship, promoting social life, quality of life and well-being. With this, the work sought to identify and map existing public spaces in Sergipe cities, and from this identification point out the limits and overcomings for the democratization of access to these spaces and guidance to the population, thus contributing to the decision-making of public managers in the combating sedentary lifestyles and raising the population’s sports culture. The study uses a qualitative approach, performing data collection through field research, applying a semi-structured questionnaire and field diary in nine cities in Sergipe. Few surveyed squares have a police module, medium and strong rumors of evidenced use of drugs, alcohol and robberies, most of these places have some type of damaged, unused or graffiti structure and few projects of physical/sports activities initiated by the public authorities. Economic aspects and lack of time, study, housekeeping, make many people not have an adequate physical activity routine. But, it is clear that the lack of public policies for guidance in physical activity, hinder the practical massification for the sample in question.